Accuracy of Critical Care Pain Observation Tool and Behavioral Pain Scale to assess pain in critically ill conscious and unconscious patients: prospective, observational study. Issue 1 (December 2016) - Severgnini, Paolo; Pelosi, Paolo; Contino, Elena; Serafinelli, Elisa; Novario, Raffaele; Chiaranda, Maurizio
Abstract Background Critically ill patients admitted to intensive care unit (ICU) may suffer from different painful stimuli, but the assessment of pain is difficult because most of them are almost sedated and unable to self-report. Thus, it is important to optimize evaluation of pain in these patients. The main aim of this study was to compare two commonly used scales for pain evaluation: Critical Care Pain Observation Tool (CPOT) and Behavioral Pain Scale (BPS), in both conscious and unconscious patients. Secondary aims were (1) to identifying the most relevant parameters to determine pain scales changes during nursing procedures, (2) to compare both pain scales with visual analog scale (VAS), and (3) to identify the best combination of scales for evaluation of pain in patients unable to communicate. Methods In this observational study, 101 patients were evaluated for a total of 303 consecutive observations during 3 days after ICU admission. Measurements with both scales were obtained 1 min before, during, and 20 min after nursing procedures in both conscious (n.41) and unconscious (n.60) patients; furthermore, VAS was recorded when possible in conscious patients only. We calculated criterion and discriminant validity to both scales (Wilcoxon, Spearman rank correlation coefficients). The accuracy of individual scales was evaluated. The sensitivity and the specificity of CPOT and BPS scores were assessed. Kappa coefficients with the quadratic weight were used to reflect agreement between the two scales, and we calculated the effect size to identify the strength of a phenomenon. Results CPOT and BPS showed a good criterion and discriminant validity (p  < 0.0001). BPS was found to be more specific (91.7 %) than CPOT (70.8 %), but less sensitive (BPS 62.7 %, CPOT 76.5 %). COPT and BPS scores were significantly correlated with VAS (p  < 0.0001). The combination of BPS and CPOT resulted in better sensitivity 80.4 %. Facial expression was the main parameter to determine pain scales changes effect size = 1.4. Conclusions In critically ill mechanically ventilated patients, both CPOT and BPS can be used for assessment of pain intensity with different sensitivity and specificity. The combination of both BPS and CPOT might result in improved accuracy to detect pain compared to scales alone. Trial registration NCT01669486